High wage workers match with high wage firms: Clear evidence of the effects of limited mobility bias - Martyn J. Andrews; Leonard Gill; Thorsten Schank; Richard Upward (Institute for the Study of Labor (IZA), 2012)
Positive assortative matching implies that high productivity workers and firms match together. However, there is almost no evidence of a positive correlation between the worker and firm contributions in two-way fixed-effects wage equations. This could be the result of a bias caused by standard estimation error. Using German social security records we show that the effect of this bias is substantial in samples with limited inter-firm movement. The correlation between worker and firm contributions to wage equations is unambiguously positive.
Keywords: J20; J30; C23; 330; linked employer-employee panel data; fixed effects; limited mobility bias; Lohnkurve; Arbeitskräfte; Arbeitsproduktivität; Unternehmen; Produktivität; Matching; Arbeitsmobilität; Bias; Schätzung; Deutschland